Effects of test levels on creep and relaxation characteristic parameters of stem for rice seedlings grown in plastic cell tray - Xiao, Jinqing; Ma, Ruijun; Chen, Yu (International Journal of Agricultural and Biological Engineering, 2020)
Creep and relaxation characteristics of stem for rice seedlings grown in plastic cell tray were studied by static tensile testing, in order to determine the relationship between characteristic parameters (rheological model parameters, stress components and strain components) and test levels (stress levels and strain levels). Rice seedling stem specimen used in the test was 40 mm in length. And the applied test values for the creep and relaxation test ranged from 1.0-3.0 MPa and 1.5%-3.5%, respectively, each for 5 levels. The results indicated that elastic modulus in the creep and relaxation model was not affected by test levels. However, except that viscosity coefficient ηkv was a constant and ηm1 decreased with the increase of test levels, other viscosity coefficient and rheological time nonlinearly increased as the test levels increased. And strain components in the creep model and stress components in the relaxation model significantly increased as the test levels increased.Keywords: model parameters, rheological property, stress relaxation, creep property, rice seedling stem, plastic cell trayDOI: 10.25165/j.ijabe.20201304.5673Citation: Xiao J Q, Ma R J, Chen Y. Effects of test levels on creep and relaxation characteristics parameters of stem for rice seedling grown in plastic cell tray. Int J Agric & Biol Eng, 2020; 13(4): 19–28.